Exploring Vaccine Hesitancy, Structural Barriers, and Trust in Vaccine Information Among Populations Living in the Rural Southern United States - Alice R. Richman; Abby J. Schwartz; Sarah B. Maness; Leslie Sanchez; Essie Torres (Vaccines)
Introduction: In the United States, vaccine hesitancy is higher among rural and racially and ethnically diverse communities, and messaging from trusted individuals may increase vaccine acceptance. The purpose of this study is to understand vaccine hesitancy, messaging from trusted individuals, and vaccine acceptance strategies among racially and ethnically diverse, medically underserved rural populations. Methods: The researchers conducted 12 in-person focus groups, each consisting of 5 to 12 participants, with community members and trusted leaders from three rural counties in Eastern North Carolina (n = 119). Thematic analysis was used to synthesize insights from the discussions, allowing for the identification of recurring patterns and community-specific considerations regarding vaccine perceptions and messaging. Results: The researchers identified seven key themes within the primary focus areas of the study: factors influencing vaccine hesitancy, messaging from trusted individuals, and strategies to improve vaccine acceptance. Participants reported differences in trust based on how long a vaccine has been available, concerns about becoming sick after a vaccine, seeing the symptoms of vaccine-preventable diseases, and misinformation on social media. Overall, participants reported trust in messages from medical providers. Trusted leaders advised people to conduct their own research on vaccines when determining whether to receive vaccinations. Lastly, social determinants such as cost, education, and transportation were identified as key barriers to vaccination. Conclusions: Our findings indicate that medical providers are trusted messengers for vaccine information and the promotion of vaccine uptake. However, distrust linked to fear, misinformation, and structural barriers persist. Public health efforts to increase vaccination confidence among rural, racially and ethnically diverse populations in the United States Southeast should address these factors in future vaccine interventions and educational efforts.